Multiomics profiling reveals VDR as a central regulator of mesenchymal stem cell senescence with a known association with osteoporosis after high-fat diet exposure - Jiayao Chen; Shuhong Kuang; Jietao Cen; Yong Zhang; Zongshan Shen; Wei Qin; Qiting Huang; Zifeng Wang; Xianling Gao; Fang Huang; Zhengmei Lin (Nature Publishing Group, 2024)
Abstract The consumption of a high-fat diet (HFD) has been linked to osteoporosis and an increased risk of fragility fractures. However, the specific mechanisms of HFD-induced osteoporosis are not fully understood. Our study shows that exposure to an HFD induces premature senescence in bone marrow mesenchymal stem cells (BMSCs), diminishing their proliferation and osteogenic capability, and thereby contributes to osteoporosis. Transcriptomic and chromatin accessibility analyses revealed the decreased chromatin accessibility of vitamin D receptor (VDR)-binding sequences and decreased VDR signaling in BMSCs from HFD-fed mice, suggesting that VDR is a key regulator of BMSC senescence. Notably, the administration of a VDR activator to HFD-fed mice rescued BMSC senescence and significantly improved osteogenesis, bone mass, and other bone parameters. Mechanistically, VDR activation reduced BMSC senescence by decreasing intracellular reactive oxygen species (ROS) levels and preserving mitochondrial function. Our findings not only elucidate the mechanisms by which an HFD induces BMSC senescence and associated osteoporosis but also offer new insights into treating HFD-induced osteoporosis by targeting the VDR-superoxide dismutase 2 (SOD2)-ROS axis.